Topical ocular application of aggrelyte-2A reduces lens stiffness in mice - Panja, Sudipta; Nam, Mi-Hyun; Gaikwad, Hanmant; Rankenberg, Johanna; Nagaraj, Ram H. (Frontiers in Ophthalmology, 2023)
Presbyopia is the progressive loss of the ability of the lens to focus on nearby objects due to its increased stiffness. It occurs in the mid-40s and continues to worsen until the mid-60s. The age-associated increase in protein cross-linking in the lens leads to protein aggregation and water insolubility, especially in the nuclear region, contributing to lens stiffness. This study reports the development of aggrelyte-2A (methyl S-acetyl-N-(3,3-dimethylbutanoyl) cysteinate, a derivative of our previously reported aggrelyte-2) for reversing the stiffness of aged lenses. Aggrelyte-2A showed minimal toxicity in cultured mouse lens epithelial cells (up to 2000 µM) and human lens epithelial cells (up to 250 µM). Lenses from aged mice (age: 24-25 months) treated with 1 mM aggrelyte-2A for 24 h, and human lenses (age: 47-67 years) treated with 250 µM aggrelyte-2A for 48 h showed 11-14% reductions in stiffness, accompanied by an increase in acetyllysine in lens proteins, and free-thiols in the lens. Topical application of aggrelyte-2A (40 mM, 5 µl twice daily for 4 weeks) on mouse eyes significantly reduced lens stiffness. The topical application showed no toxicity to the lens, cornea, or retina, as revealed by morphological examination, H&E staining, and optical coherence tomography. These data suggest that aggrelyte-2A could be developed as a presbyopia-reversing therapeutic.